KAJIAN TENTANG SISTEM PENDETEKSIANSEL DARAH PUTIH MENGGUNAKAN METODE SCALE INFARIANT FEATURE TRANSFORM - Johan Johan; Lina Lina; Arlends Chris (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Technological advances in the world of information in all areas of life science includes medical information. Detecting white blood cell is important to indicate cause of illness. This paper present a system using SIFT (Scale Infariant Feature Transform) method to detect the white blood cells. As a system, user can input a picture of blood cell and the system will automaticaly give an output be in the form of cropped picture.